If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 6r + -7r = 7r + 3 + -2r Combine like terms: 6r + -7r = -1r 8 + -1r = 7r + 3 + -2r Reorder the terms: 8 + -1r = 3 + 7r + -2r Combine like terms: 7r + -2r = 5r 8 + -1r = 3 + 5r Solving 8 + -1r = 3 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. 8 + -1r + -5r = 3 + 5r + -5r Combine like terms: -1r + -5r = -6r 8 + -6r = 3 + 5r + -5r Combine like terms: 5r + -5r = 0 8 + -6r = 3 + 0 8 + -6r = 3 Add '-8' to each side of the equation. 8 + -8 + -6r = 3 + -8 Combine like terms: 8 + -8 = 0 0 + -6r = 3 + -8 -6r = 3 + -8 Combine like terms: 3 + -8 = -5 -6r = -5 Divide each side by '-6'. r = 0.8333333333 Simplifying r = 0.8333333333
| =(y-5)(y-3) | | A^3b^2= | | 4c^2+24c+30=0 | | =x^3-27 | | 2x+[3x-2(x-2y)-3x]= | | =15a^2+11a+2 | | 9x+6+4x+x-9= | | -3x-(2-x)=-2(2-3x) | | 13(t-4)+8t=7(3t+5)-8 | | 3(y+5)+5(y-4)+7= | | 15x^2-26x=0 | | 7(x-3)=7-2(3x+1) | | 4(y-5)= | | 9X+7X=81+X | | 3-2(4-x)=5(x+1)+2 | | 4mn-6m+5n-3m+4n-5mn= | | =x^2+19x+2 | | 2(x-3)-(x-2)=2x+3 | | 1-7y=-1 | | x-8.7=6.8 | | -9.3x=55.8 | | m+33=13 | | 24(2x-1)=6(x+3)+3 | | 2r=-8 | | =2-3x+2x^2-x^3 | | (4x-1)(x+2)=x(2x-3)-10 | | -8(2b+4)+(17b-6)=0 | | 2.5q-4.8-4.1q=-2.6q-4.7 | | 4-(2-3x)=6x-(4x+3) | | 0=-8+3z | | 2.5q-4.8q-4.1q=-2.6q-4.7 | | =2x^7+4x^6-6x^5+4x^4 |